2003
DOI: 10.1197/aemj.10.8.872
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Adult versus Adolescent Sexual Assault: Epidemiology and Patterns of Anogenital Injury

Abstract: Objectives: To compare the characteristics of sexual assault in pubertal girls (\18 years old) and adults in a communitybased population of women presenting to an urban sexual assault clinic. Methods: This case-series analysis evaluated consecutive female patients presenting to a sexual assault clinic during a three-year study period. The clinic is associated with a university-affiliated emergency medicine residency program and is staffed by forensic nurses trained to perform medicolegal examinations using col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 17 publications
2
28
1
1
Order By: Relevance
“… Note . Cervical trauma in the Jones et al (2003) study and Rossman et al (2004) is read from a bar graph and approximate. Anal injuries and non‐genital results not reported here. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… Note . Cervical trauma in the Jones et al (2003) study and Rossman et al (2004) is read from a bar graph and approximate. Anal injuries and non‐genital results not reported here. …”
Section: Methodsmentioning
confidence: 99%
“…Jones et al (2003) compared 766 consecutive female rape victims over a 3‐year period (1999 to 2001). The sample had 57% adult victims (18 years and over) and 43% adolescent victims (between the ages of 13 to 17 years).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The head‐to‐toe examination of a comatose patient should include assessment of the ano‐genital area for acute traumatic injury, bleeding, or foreign material. Because ano‐genital injury rates after sexual assault range from 12% to 83% depending on the studies and variables examined (Magid et al, 2004; Jones, Rossman, Wynn, Dunnuck, & Schwartz, 2003), it is important that a trained examiner assess the area, and that the examination occur before activities such as bladder catheterization, which may interfere with the ability of the examiner to effectively recover biological evidence.…”
Section: Standard Of Carementioning
confidence: 99%
“…This issue is important to examine because, although the forensic components for adult and adolescent examinations are similar, recent research has found that adolescents differ from adults with respect to anogenital injuries (Jones, Rossman, Wynn, Dunnuck, & Schwartz, 2008), indicating that these populations may have distinct healthcare needs. This issue is important to examine because, although the forensic components for adult and adolescent examinations are similar, recent research has found that adolescents differ from adults with respect to anogenital injuries (Jones, Rossman, Wynn, Dunnuck, & Schwartz, 2008), indicating that these populations may have distinct healthcare needs.…”
mentioning
confidence: 99%